GOD OF COMPASSION AND THE DIVINE PROTECTOR OF 'SRI PADA': TRENDS IN POPULAR BUDDHISM IN SRI LANKA - De Silva, Premakumara (My University, 2008)
Theravada Buddhism in Sri Lanka has always coexisted with various forms of other religious practices oriented to deities, planets, astrology and demons (yakku), and some of these often figure in the Hindu tradition as well. However, the Buddhist doctrine in its canonical form stands apart from the culturallyspecific forms of popular religious practices. Beliefs in gods and other supernatural powers and rituals are, in theory, inappropriate to be considered as part of Buddhism. But many anthropologists and sociologists who have spent extended periods of time in Theravada Buddhist societies have shown that Buddhists do believe in various types of supernatural powers and the magical efficacy of rituals which are outside the Buddhist doctrine. According to Obeyesekere (1962) astrology, gods and demon belief in 'Sinhala Buddhism' are guided by basic Buddhist principles such as karma, rebirth, suffering etc. So in that sense the practice of deity worship cannot be described as totally un- Buddhistic, yet at the same time it does not fall into the category of folk religious practices like bali and tovil adopted by popular Buddhism (see De Silva 2000, 2006). In Sri Lanka. there are four deities regarded as the guardians of the Buddha-sasana in the island: Vishnu, Saman, Kataragama, Natha and Pattini. Although Vishnu and Kataragama (Skanda) are originally Hindu gods, the Buddhists have taken them over as Buddhist deities, referring to them also by the localized designation, Uppalavanna and Kataragama. The role of Kataragama, Vi1inI1U,Natha and Pattini worship in the contemporary Sri Lankan society has been well researched by several scholars (e.g., Obeyesekere 1984; Holt 1991,2005; Gunasekara 2007) but the position of god Saman in the similar context has not been adequately investigated. Hence this paper explores the rise of the popularity of god Saman and his worship in contemporary Sri Lanka.
Keywords: GOD OF COMPASSION AND THE DIVINE PROTECTOR OF 'SRI PADA': TRENDS IN POPULAR BUDDHISM IN SRI LANKA